2022
DOI: 10.1039/d2sc04843d
|View full text |Cite
|
Sign up to set email alerts
|

Coordination-induced bond weakening of water at the surface of an oxygen-deficient polyoxovanadate cluster

Abstract: Hydrogen-atom (H-atom) transfer at the surface of heterogeneous metal oxides has received significant attention owing to its relevance in energy conversion and storage processes. Here, we present the synthesis and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 87 publications
6
27
0
Order By: Relevance
“…Next, we set out to determine the BDFE(O–H) avg of the aquo ligand bound to a second O-atom deficient site at the surface of the assembly (Scheme 2). Despite the quantitative transfer of the H-atoms from Hydz (BDFE(N–H) avg = 60.4 kcal mol −1 ) 15,30 to [V 6 O 7 ] 0 , exposure of this reductant to [V 6 O 6 (MeCN)] 0 in THF-d 8 results in only partial conversion to the di-vacant cluster, [V 6 O 5 (MeCN)(OH 2 )(OCH 3 ) 12 ] 0 ( [V 6 O 5 (MeCN)(OH 2 )] 0 ) (Fig. S9†).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we set out to determine the BDFE(O–H) avg of the aquo ligand bound to a second O-atom deficient site at the surface of the assembly (Scheme 2). Despite the quantitative transfer of the H-atoms from Hydz (BDFE(N–H) avg = 60.4 kcal mol −1 ) 15,30 to [V 6 O 7 ] 0 , exposure of this reductant to [V 6 O 6 (MeCN)] 0 in THF-d 8 results in only partial conversion to the di-vacant cluster, [V 6 O 5 (MeCN)(OH 2 )(OCH 3 ) 12 ] 0 ( [V 6 O 5 (MeCN)(OH 2 )] 0 ) (Fig. S9†).…”
Section: Resultsmentioning
confidence: 99%
“…However, in comparing the enthalpies of activation (Δ H ‡ ) of H-atom transfer to fully oxygenated and O-atom deficient POV–alkoxide clusters, we note a significant discrepancy; while both values are consistent with previously reported CPET reactions to metal oxide surfaces, the small Δ H ‡ associated with formation of [V 6 O 5 (MeCN)(OH 2 )] 0 indicates that less energy is required for bond weakening processes relevant to the formation of the transition state. 14–16,18,20,42,43…”
Section: Resultsmentioning
confidence: 99%
“…Previous work from our group has demonstrated that PCET to these electron deficient vanadium-oxo moieties results in the irreversible formation of an O-atom vacancy. 32,33 We thus hypothesized that chemical reduction would provide the opportunity to improve the selectivity of this process; reduction of the number of organosaturated V V =O centres available for O-atom defect formation would translate to localization of net H-atom installation to the more basic, bridging oxide site.…”
Section: Resultsmentioning
confidence: 99%
“…The operative form of net H-atom addition to these organofunctionalized assemblies involves activation of a terminal V]O moiety, resulting in the formation of an unstable hydroxide which abstracts an additional H-atom equivalent to generate a labile aquo ligand at the surface of the cluster. 32,33 We hypothesize that the observed localization of net H-atom uptake at O t groups is a consequence of organic saturation of the bridging oxide positions at the surface of the assembly (i.e. m 2 -OMe 1− as opposed to m 2 -O 2− ).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of terminal M IV -OH 2 species at the mixed Mo/W triad can be viewed as the uptake of H-atom equivalents (protons and electrons) into the POM. This behavior should not be assumed to be characteristic of POMs built from group VI transition-metal centers, indeed Matson and co-workers nicely showed that Lindqvist-type polyoxovanadates also exhibit proton-coupled electron-transfer reactivities. We think that the potential benefits of Mo–W bonds in reduced POMs is the modification of the metal–metal bond polarity, which could have a large influence on the reactivity of “heteropoly brown”, especially in the context of H-atom-transfer reactions. In addition to the formation of heterometallic metal–metal bonds in POMs, this work shows that the reduction-induced aquation of the POM strongly affects its supramolecular behavior, canceling its chaotropic character.…”
Section: Discussionmentioning
confidence: 99%